The Rise and Fall of African Rice Cultivation Revealed by Analysis of 246 New Genomes - (:unkn) unknown (My University, 2018)
African rice (Oryza glaberrima) was domesticated independently from Asian rice. The geographical origin of its domestication remains elusive. Using 246 new whole-genome sequences, we inferred the cradle of its domestication to be in the Inner Niger Delta. Domestication was preceded by a sharp decline of most wild populations that started more than 10.000 years ago. The wild population collapse occurred during the drying of the Sahara. This finding supports the hypothesis that depletion of wild resources in the Sahara triggered African rice domestication. African rice cultivation strongly expanded 2.000 years ago. During the last five centuries, a sharp decline of its cultivation coincided with the introduction of Asian rice in Africa. The gene PROG1 associated with an erect plant architecture phenotype, showed convergent selection in two rice cultivated species, Oryza glaberrima from Africa and Oryza sativa from Asia. In contrast, the shattering gene SH5 showed selection signature during African rice domestication, but not during Asian rice domestication. Overall, our genomic data reveal a complex history of African rice domestication influenced by important climatic changes in the Saharan area, by the expansion of African agricultural society, and by recent replacement by another domesticated species.
Keywords: African Research